2018
DOI: 10.1002/bimj.201700211
|View full text |Cite
|
Sign up to set email alerts
|

BMA‐Mod: A Bayesian model averaging strategy for determining dose‐response relationships in the presence of model uncertainty

Abstract: Successful pharmaceutical drug development requires finding correct doses. The issues that conventional dose-response analyses consider, namely whether responses are related to doses, which doses have responses differing from a control dose response, the functional form of a dose-response relationship, and the dose(s) to carry forward, do not need to be addressed simultaneously. Determining if a dose-response relationship exists, regardless of its functional form, and then identifying a range of doses to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…According to 1 showed that the correlation matrix in the model of factors affecting the willingness to join crop insurance. Gould, 2018), the LR statistical test, according to the Chi-square distribution, is 167.47 and the probability value Pr (> Chi2) <0.0001 so the Ho hypothesis is rejected. The five factors included in the Logistic model are important for insurance.…”
Section: Estimated Results Of Logistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to 1 showed that the correlation matrix in the model of factors affecting the willingness to join crop insurance. Gould, 2018), the LR statistical test, according to the Chi-square distribution, is 167.47 and the probability value Pr (> Chi2) <0.0001 so the Ho hypothesis is rejected. The five factors included in the Logistic model are important for insurance.…”
Section: Estimated Results Of Logistic Regressionmentioning
confidence: 99%
“…According to (Wang, D., Zhang, W., Bakhai, A, 2004), a Bayesian solution to the model's uncertainty has been proposed and applied recently (A. Lawrence Gould, 2018). This method selects a subset of all possible models (max K = 2 p , ignoring interactions between explanatory variables) (Krzysztof Drachal, 2018) .…”
Section: Summary Of Bayesian Model Averaging (Bma) Followingmentioning
confidence: 99%
“…, where s i is an element of s, and 𝛼 (1) , 𝛽 (1) , 𝛼 (2) , 𝛽 (2) , 𝛼 (3) , 𝛽 (3) are the parameters of the DNN. We estimate 𝜋 * using reinforcement learning.…”
Section: Deep Reinforcement Learningmentioning
confidence: 99%
“…In addition, some parts of a curve can be fixed, while others modeled more flexibility. A parametric framework offers two approaches to fitting when the shape of a curve is not known in advance: model averaging 7 and model selection. Both approaches start with a set of parametric models and then undergo two stages.…”
Section: Introductionmentioning
confidence: 99%